Teaching Literacies in Diverse Contexts - Harmey, Sinead; Kabuto, Bobbie (UCL Press, 2023)
Literacy education can take place in many locations and periods across the lifespan. Literacy educators require flexibility and a deep toolbox to meet their students' diverse needs, regardless of whether they work in traditional school and college settings or in other environments with varied populations. Teaching Literacy in Diverse Contexts showshow practical experiences can be used in creative ways to support educator development for teaching literacy in a global context. Mentorship between a developing literacy educator and an experienced teacher educator is central to the book, and to the practical experiences in training or professional development that it focuses on. Chapters share the creative solutions discovered during mentorship that supported developing literacy educators to teach with authenticity in a number of contexts, including the adult learning sector, a rural community in Africa and alongside parents of very sick children. The authors demonstrate how this can be done in a sensitive and culturally relevant manner by parents, volunteers and teachers with varying degrees of experience in both formal and informal spaces. Together, the chapters build a crucial resource for preparing a broad range of literacy educators to teach literacy in many contexts where policy on how best to teach reading and writing to diverse student bodies ebbs and flows.